Pseudopontixanthobacter vadosimaris gen. nov., sp. nov., isolated from shallow sea near Kueishan Island. Issue 12 (11th December 2020) - Sun, Jia; Guo, Jiaying; Lin, Ta-Hui; Feng, Xuejin; Zhang, Rui
Abstract : A Gram-stain-negative and aerobic bacterial strain, designated as JL3514 T, was isolated from surface water of the hydrothermal system around Kueishan Island. The isolate formed red colonies and cells were non-flagellated, rod-shaped and contained methanol-soluble pigments. Growth was observed at 10–50 °C (optimum, 30 °C), at pH 5.0–9.0 (optimum, pH 7.0) and in the presence of 0–9 % (w/v) NaCl (optimum, 2 %). Strain JL3514 T was positive for catalase and weakly positive for oxidase. Results of 16S rRNA gene sequence analyses showed highest similarities to species in the family Erythrobacteraceae, namely Croceibacterium atlanticum (96.1 %), Pelagerythrobacter marensis (96.0 %), Tsuneonella rigui (96.0 %) and Altericroceibacterium xinjiangense (96.0 %). Phylogenetic analysis based on core gene sequences revealed that the isolate formed a distinct branch with the related species and it had a lower average amino acid identity value than the suggested threshold for genera boundaries. The major fatty acids (>5 %) were summed feature 8 (C18 : 1  ω 7 c and/or C18 : 1  ω 6 c ), summed feature 3 (C16 : 1  ω 7 c and/or C16 : 1  ω 6 c ), C16 : 0, C17 : 1  ω 6 c, C14 : 0 2-OH and C12 : 0 . The dominant polar lipids comprised diphosphatidylglycerol, sphingoglycolipid, phosphatidylethanolamine, phosphatidylglycerol, phosphatidylcholine, glycolipid, two unidentified lipids and one unidentified phospholipid. The main respiratory quinones were ubiquinone-10 (95.7 %) and ubiquinone-9 (4.3 %). The DNA G+C content from the genome was 63.0 mol%. Based on the presented data, we consider strain JL3514 T to represent a novel genus of the family Erythrobacteraceae, with the name Pseudopontixanthobacter vadosimaris gen. nov., sp. nov. The type strain is JL3514 T (=KCTC 62623 T =MCCC 1K03561 T ).